Determinants of adherence to antiretroviral therapy among people living with HIV/AIDS in Chhattisgarh, India - Khede, Mayank Kumar; Parija, Pragyan Paramita; Madhukar, Manisha Ruikar; Bhinjwar, Shiv Kumar (International Journal Of Community Medicine And Public Health, 2021)
Background: Achieving the WHO 2020 treatment goals will not only depend on access to HIV treatment, but also on good adherence. Chhattisgarh SACS under guidance of CST division NACO and community and family medicine department AIIMS, Raipur undertook this study to investigate the major factors that influence the adherence of PLHIV visiting ART centres of Chhattisgarh. Methods: From five ART centres, 415 participants were interviewed through simple random sampling method through a semi structured interview schedule. Results: We found that 346 of the 415 (83.3%) patients had ≤95% adherence to ART on the basis of pill count method. Major proportion (90.0%) of patients were on TLE regimen, among them (74.4%) were non-adherent. An association was found between health condition of patient, poor life style and adherence rate. Three-month drug dispensation was recommended by most of the participants to improve adherence. Conclusions: Multiple months drug dispension along with other innovative approaches should be tailored made to improve the adherence and compliance among PLHIV individuals.